So close, yet so far away: the relationship between MAM and cardiac disease - Bo Lu; Bo Lu; Xiaozhe Chen; Xiaozhe Chen; Yulong Ma; Mingtai Gui; Lei Yao; Jianhua Li; Mingzhu Wang; Xunjie Zhou; Xunjie Zhou; Deyu Fu; et al. (Frontiers in Cardiovascular Medicine, 2024)
Mitochondria-associated membrane (MAM) serve as crucial contact sites between mitochondria and the endoplasmic reticulum (ER). Recent research has highlighted the significance of MAM, which serve as a platform for various protein molecules, in processes such as calcium signaling, ATP production, mitochondrial structure and function, and autophagy. Cardiac diseases caused by any reason can lead to changes in myocardial structure and function, significantly impacting human health. Notably, MAM exhibits various regulatory effects to maintain cellular balance in several cardiac diseases conditions, such as obesity, diabetes mellitus, and cardiotoxicity. MAM proteins independently or interact with their counterparts, forming essential tethers between the ER and mitochondria in cardiomyocytes. This review provides an overview of key MAM regulators, detailing their structure and functions. Additionally, it explores the connection between MAM and various cardiac injuries, suggesting that precise genetic, pharmacological, and physical regulation of MAM may be a promising strategy for preventing and treating heart failure.